2011
DOI: 10.1017/s0033291711002212
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of childhood maltreatment on associations between social information processing and adult aggression

Abstract: Background Associations between early life maltreatment, social information processing (SIP) and aggression in childhood and adolescence have been widely documented. Few studies have examined the importance of childhood maltreatment independent of SIP in the etiology of adult aggression. Furthermore, moderating effects of childhood maltreatment on the SIP–aggression links have not been explored. Method Hierarchical, multi-level models were fitted to data from n=2752 twins aged 20–55 years from the PennTwins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 68 publications
4
27
0
3
Order By: Relevance
“…Therefore, the well-documented influence of different forms of childhood maltreatment on potential for violence was replicated [1,7,8,25,31,84]. Against our hypothesis in the present analysis, attachment was not influenced by childhood maltreatment and did not influence potential for violence.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, the well-documented influence of different forms of childhood maltreatment on potential for violence was replicated [1,7,8,25,31,84]. Against our hypothesis in the present analysis, attachment was not influenced by childhood maltreatment and did not influence potential for violence.…”
Section: Discussionsupporting
confidence: 74%
“…Childhood maltreatment is, among other consequences, closely linked to the development of a heightened potential for violence [6,7,8]. Specifically, experiences of childhood maltreatment are associated with the development of an increased level of aggressive behavior in the maltreated child or adolescent [9,25] and an increased risk of developing CD [2,7,26]. While some authors argue that physical punishment exerted by loving parents does not entail negative consequences for the child [27,28], the present study does not differentiate between physical maltreatment and physical punishment since the main body of research emphasizes the negative outcomes of physical punishment or abuse, respectively, with regard to externalizing behavior and heightened aggression [1,29,30,31,32].…”
Section: Childhood Maltreatment and Potential For Violencementioning
confidence: 99%
“…Other researchers have examined two main types of social information processing, hostile attribution biases and negative emotional responses that influence aggression in adulthood (Chen, Coccaro, Lee & Jacobson, 2012). They found that individuals who had experienced more severe childhood maltreatment and emotional abuse/neglect were aggressive in adulthood when they reported having more negative emotional responses, in comparison to those who experienced little/no abuse.…”
Section: Predictive Factors Of Domestic Violence Offending 10mentioning
confidence: 99%
“…Attributions stem from our attempts to understand the causes of events (Heider, 1958), and early maltreatment has been shown to influence one’s attributional style (Buser & Hackney, 2012; Chen, Coccaro, Lee, & Jacobson, 2012). Research to date has focused on the effects of childhood emotional abuse on negative cognitive styles mostly as they pertain to deleterious evaluations about oneself (Gibb & Abela, 2008).…”
Section: Emotional Abuse and Empathic Accuracymentioning
confidence: 99%